The Impact of Mobile Phone Use on Young Drivers’ Driving Behaviour and Visual Scanning of the Environment - Babić, Darko; Prelčec, Ivana; Babić, Dario; Boroša, Vanna; Fiolić, Mario (Promet - Traffic&Transportation, 2022)
Driver distraction has been identified as a contributing factor to road crashes, among which the most common is the use of mobile phones while driving. For this reason, the aim of this paper is to analyse the behaviour of young drivers while they use mobile phones (answering a telephone call, texting, and browsing the internet) and drive in a simulated urban environment. In total 28 volunteers participated in the study. Several variables were recorded for each participant: driving speed, acceleration, deceleration, and eye movement. The results show that the difference in driving speed, acceleration, and deceleration was relatively small for each task and for the control condition (no use of mobile phone). However, when looking at the total time required for conducting each task, participants spent 26.44% of the time looking at the phone when texting, 37.01% when browsing the internet, and 2.27% when talking on the phone. In addition, participants viewed on average 66.45% traffic signs when distracted, compared to 79.22% during undistracted driving. Based on the results, a proactive approach to reduce the problem related to the use of mobile phones while driving is proposed.